2018
DOI: 10.1038/mi.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant selection regulates gut migration and phenotypic diversity of antigen-specific CD4+ T cells following parenteral immunization

Abstract: Infectious diarrheal diseases are the second leading cause of death in children under five, making vaccines against these diseases a high priority. It is known that certain vaccine adjuvants, chiefly bacterial ADP-ribosylating enterotoxins, can induce mucosal antibodies when delivered parenterally. Based on this, we reasoned vaccine-specific mucosal cellular immunity could be induced via parenteral immunization with these adjuvants. Here, we show that, in contrast to the TLR9 agonist CpG, intradermal immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…6 to the gut after parenteral immunization. 52 Adjuvant selection may also be important for generating T RM in the nasopharynx. In support of this notion, Allen et al recently demonstrated that the choice of adjuvant influenced the generation of CD4 + T RM in the lung following parenteral immunization with an acellular proteinbased pertussis vaccine, although whether these lung CD4 + T RM were truly antigen-specific was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…6 to the gut after parenteral immunization. 52 Adjuvant selection may also be important for generating T RM in the nasopharynx. In support of this notion, Allen et al recently demonstrated that the choice of adjuvant influenced the generation of CD4 + T RM in the lung following parenteral immunization with an acellular proteinbased pertussis vaccine, although whether these lung CD4 + T RM were truly antigen-specific was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…microneedles, therefore bypassing the constraints associated with enteropathy and the requirements for a cold chain. 101 Alternative, potentially low-cost strategies for vaccine production and storage such as transgenic plants seem to be gaining traction as exemplified by the oral delivery of rice expressing cholera toxins. 70 In principle, this approach could also be explored for Rotavirus vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Only antigen-specific IgG was present in lung mucosal fluid after intradermal immunization while both IgG and IgA were detected after intranasal delivery. 100 Frederick et al 101 compared the effect of CpG and dmLT in combination with MHC class II CD4 + T cell peptide antigen 2W1S after intramuscular and intradermal ear immunization in mice. dmLT was superior to CpG for expanding and maintaining antigen-specific CD4 + T cells in lymph nodes and spleen and at inducing intestinal homing integrin α4β7 in spleen and mesenteric lymph nodes.…”
Section: Mucosal Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, dmLT has shown promise as an adjuvant that redirects parenterally administered vaccines to an immune response in the gut. 108 It is our hope that ongoing efforts to develop a safe and immunogenic ST toxoid capable of inducing strong mucosal immune responses in the human gut can importantly complement ETEC vaccine candidates currently in the pipeline to produce a broadly protective ETEC vaccine that can substantially reduce the diarrheal disease burden in LMIC children.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%